Pioneer Shipping and Sea Toll Ships Support National Logistics Distribution Program: Study Literature Review - Prasidi, Abi (Siber Journal of Transportation and Logistics, 2025)
Efficiency and equitable distribution of logistics are key elements in supporting national economic development, especially in an archipelagic country like Indonesia. This article explores the contribution of pioneer shipping and sea toll ships in strengthening the national logistics system. Pioneer shipping plays a vital role in opening up access to sea transportation to hard-to-reach areas, such as remote, outermost, and disadvantaged areas, which commercial shipping lines have not served. Meanwhile, the sea toll program is present as a solution to reduce price disparities between regions through regular and low-cost delivery of goods. This study uses a descriptive qualitative approach with case studies on several pioneer shipping routes and sea toll routes. The study results show that both programs significantly impact expanding connectivity, driving the local economy, strengthening the national logistics system, and supporting equitable development. However, obstacles are still found, such as unbalanced cargo flows, limited supporting port facilities, and lack of coordination between stakeholders. To address these challenges, it is necessary to strengthen collaboration between the central government, local governments, and the private sector. This article provides relevant insights for other archipelagic countries that want to develop an inclusive, efficient, and sustainable maritime logistics system.